Helping people discontinue long-term antidepressants: views of health professionals in UK primary care - Tony Kendrick; Geraldine Leydon; Carl R May; Hannah M Bowers; Adam W A Geraghty; Emma Maund; Wendy O’brien (BMJ Open)
Objective The aims of this paper were to identify, characterise and explain clinician factors that shape decision-making around antidepressant discontinuation in UK primary care.Design Four focus groups and three interviews were conducted and analysed using thematic analysis.Participants Twenty-one general practitioners (GPs), four GP assistants, seven nurses and six community mental health team workers and psychotherapists took part in focus groups and interviews.Setting Participants were recruited from seven primary care regions and two National Health Service Trusts providing community mental health services in the South of England.Results Participants highlighted a number of barriers and enablers to discussing discontinuation with patients. They held a range of views around responsibility, with some suggesting it was the responsibility of the health professional (HP) to broach the subject, and others suggesting responsibility rested with the patients. HPs were concerned about destabilising the current situation, discussed how continuity and knowing the patient facilitated discontinuation talks, and discussed how confidence in their professional skills and knowledge affected whether they elected to raise discontinuation in consultations.Conclusions Findings indicate a need to consider support for HPs in the management of antidepressant medication and discussions of discontinuation in particular. They may also benefit from support around their fears of patient relapse and awareness of when and how to initiate discussions about discontinuation with their patients.